Al-Ghazālī's conception of the purification of the self: Reflections from Iḥyā’ ‘Ulūm al-Dīn (revival of the religious knowledge) - Helwa, Soha Ahmad (AUC Knowledge Fountain, 2017)
Al-Ghazālī's name and his book Iḥyā’ ‘Ulūm al-Dīn are attached to self-purification, which is an essential part in the religion of Islam. This study does not seek to analyze all the details of Al-Ghazālī's program to purify the self. Rather, it focuses on delineating a framework - from Iḥyā’ ‘Ulūm al-Dīn - concerning his understanding of self-purification. This framework mainly includes his method of purifying the self. In the midst of this, many of Al-Ghazālī's psychological insights are extracted, under the umbrella of the Islamic perspective of psychology. Among these insights are some related to his perception of the human nature. In addition, some of Al-Ghazālī's educational views are highlighted. The study's findings are manifold. One finding is that the different parts of Al-Ghazālī's scheme of purifying the self are interlinked and complementary to each other. Therefore, a profound and integrated reading of Iḥyā’ ‘Ulūm al-Dīn is required in order to get a true expression of Al-Ghazālī's conception of purifying the self in this book. As to his program of self-purification, it involves impacting the whole being of the person. Although it begins with the knowing and adopting the true beliefs, it extends to heart's states among which some are qualities accompanied by specified emotions. And accordingly, one's deeds change. Moreover, Al-Ghazālī's encouragement of the best choices to be adopted by the seeker does not prevent him from considering the different states of seekers. This attitude of him is not only applied to his own recommendations, but he advises the learned guides to follow it with the seekers. So this way reflects one of his educational views. Some other educational opinions of Al-Ghazālī are untraditional like what this study names "balance disguised in extreme" as well as the impact of the teacher's heart on the learner's heart. Al-Ghazālī puts the outcomes of purifying the self on the person in this world as the felicity of knowing and loving Allāh more, without any stopping of the acts of worship.